RELATIONSHIP OF INCENTIVES AND WORK ENVIRONMENT TO EMPLOYEES PERFORMANCE OF PT. VICTORY OFFSET PRIMA - Br Sihaloho, Ruth Devi Yuliani; Anggraini, Nenny; Ktut Silvanita (Universitas Kristen Indonesia, 2021)
Work environment and incentives are very important issues in a company. Because a less conducive work environment and unsatisfactory incentives can reduce the performance of each employee, but if the work environment is conducive and the incentives provided are very satisfactory, it will improve employee performance. This can be used as a problem point in a company.This study aims to see how the relationship between incentives and work environment on the performance of PT Victory Offset Prima employees.The type of data used in this study is quantitative data, and the analytical data used are Spearman Rank and Multiple Correlation analysis. the number of samples in the study were 74 people. Data was obtained by distributing questionnaires to employees with a counting scale using a Likert scale on the statements contained in the questionnaire to process the author's data using computer aids in the form of SPSS 18. Keywords: Incentives, Work Environment, and Employee Performance